The Effectiveness of Monopoly Game to the First Grade Students' Vocabulary Mastery at MTSN PACITAN in Academic Year of 2021/2022 - Asdinar Galuh; Samsul Hadi; Agustina Sri Hafidah (ELITE Association Indonesia, 2022)
This research aimed to find out The Effectiveness of Monopoly Game to The First Grade Students Vocabulary Mastery at MTs N Pacitan in Academic Year of 2021/2022. This research used quasi experimental research. The objective of the research was: 1) To prove the effectiveness of Monopoly Game to first grade students vocabulary mastery. The method used in this research was quasi experimental research design with parametric in quantitative study. The research instruments were pre-test and post-test. The study was divided into two groups, namely experimental class and control class. The sample used in this study consisted of 20 students of 7C as experimental class and 20 students of 7D as control class. The instruments used in this research were t-test, namely pre-test and post-test. The result of this study indicated that Monopoly Game was more effective and had significant improvement in learning vocabulary for experimental class. It could be proven from gain score of post-test in experimental class was up to 412 and control class was 138. It showed that experimental class post-test was higher than control class post-test.